Modelling entrepreneurial intention with Bayesian networks - López, Jorge; Ruiz-Ruano, Ana María (Revista de Psicología, 2015)
Entrepreneurship is nowadays considered as a key element in postindustrial societies. From a psychological point of view, entrepreneurship can be understood as an attitudinal process conditioned by entrepreneurial intention. We built, tested and used three Bayesian models designed to clarify the relationships between variables commonly associated with entrepreneurship and entrepreneurial intention. A sample of 254 undergraduate university students (73 male and 179 female), ages ranging from 18 to 50 (M = 22.47, SD = 4.11), filled in a questionnaire that registered parameters associated with entrepreneurial attitude and intention. Survey answers were used to build three Bayesian networks models which were validated and used to make predictions about the variables involved in the model. Our results show that perceived desirability, perceived feasibility, and the normative social influence derived from the family and the locus of control reliably predict entrepreneurial intention. The influence of these variables over the entrepreneurial intention was analyzed considering different scenarios, and the discovered relationships between variables where discussed from practical and theoretical points of view in the context of promoting entrepreneurial attitudes.